Mintavétel és elemzési módszerek az oktatási integrációs program hatásviszgálatában, és a hatásvizsgálatból levonható követketetések - Gábor Kézdi; Éva Surányi (Hungarian Academy of Sciences, Institute of Economics, 2010)
– The National Educational Integration Network (OOIH) launched a program in 2003 that focused on the integrated education of primary school children (grades 1 through 8) in 45 schools in Hungary. The goal of the program was to compensate for the educational disadvantages of children from poor and/or minority families by providing quality education in an integrated environment. The report on the impact evaluation of the program is available at Kézdi and Surányi (2009). The results and methods of the impact evaluation research were criticized in a paper published (in Hungarian) in Magyar Tudomány, March 2010. This study answers the criticism on sampling and methodology. A separate study addresses the issues of our measurement of non-cognitive skills. It is an interesting methodological study on its own right, regardless of the debate. In both paper we show that the critiques are unfounded. In this study we also summarize the conclusions from the impact evaluation.
Keywords: I20; I38; C81; 330; Schule; Bildungspolitik; Bewertung; Methodenkritik; Ungarn